Factors Affecting Consumer Interest In Electronic Money Usage With Theory Of Planned Behavior (TPB) - Nugroho, Anton; Najib, Mukhamad; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
There are many factors that influence consumer intention to use electronic money. Based on the theory of planned behavior, behavior intention is formed by the attitude toward behavior, subjective norms and perceived behavioral control. This research aims to analyze attitude, subjective norms and perceived behavioral control that affect consumer intention in the usage of electronic money.Data collection from respondents through a structured questionnaire by self-report. Some questions in the questionnaire were made on a Likert scale with five variations of the answers in very strongly disagreeable order to strongly agree. The respondents are 290 undergraduate students that have never used server-based electronic money. The result showed that the attitude toward behavior did not a significantly affect the behavior intention. While the subjective norms and perceived behavioral control have a significant effect on the behavior intention in the usage of electronic money.